Cyberchondria During the Coronavirus Pandemic: The Effects of Neuroticism and Optimism - Maftei, Alexandra; Holman, Andrei Corneliu (Frontiers in Psychology, 2020)
Health anxiety during the current coronavirus pandemic can be a serious psychological issue, amplified by the medical uncertainty around this disease and social isolation. As older people are especially at risk of becoming severely ill, it is important to examine the personal factors that make members of this age group more prone to health anxiety. Previous studies indicated that cyberchondria, i.e., the repeated online search for medical information, exacerbates health anxiety. The present research investigated the effect of two dispositional traits opposed in valence, i.e., optimism and neuroticism, on cyberchondria during the COVID-19 pandemic. The associations of cyberchondria with demographic factors (age, gender, and education) were also examined. A sample of 880 participants, aged 15 to 67, 65% females participated in an online survey. Results show that neuroticism, age, and feminine gender are positively associated to cyberchondria. Optimism was found to be related to cyberchondria, but this effect was qualified by a significant interaction with age. Further analysis revealed that the effect of optimism was significant only in the highest age group. Moreover, among these elderly participants, the psychologically protective influence of optimism against cyberchondria emerged as larger than the opposite effect of neuroticism. This suggests the mental benefits of encouraging a positive outlook on the current health crisis and on one’s personal resilience in facing it, especially among the elderly. Conversely, among people who use the Internet as a major source of medical information, those high in neuroticism may be more prone to cyberchondria.